PENERAPAN PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN MENUNJUKKAN UANG PADA PESERTA DIDIK TUNAGRAHITA - Ega Edva Nurusyifa' Hartono (LPPM Universitas Muhammadiyah Bulukumba, 2023)
Students with intelectual disability have obstacles in academic aspects including in showing nominal rupiah currency. This research was conducted based on the difficulties of grade 6 intelectual disability students in Karangrejo Madiun SLBN. To increase the knowledge of students with intelectual disability in understanding nominal money, the learning approach must be oriented to the problems that exist in students, and involve students to be actively involved in learning. Therefore, researchers will conduct classroom action research by applying the Problem Based Learning (PBL) approach to improve learning outcomes about nominal money for intelectual disability students at SLBN Karangrejo Madiun. The method used in this research is classroom action research. Based on the research conducted, it showed that the pre-test results showed a class average of 25% with less criteria, in cycle I the class average results increased to 62.5%, with sufficient criteria. In cycle II the class average increased to 93.75% with very good criteria. This shows that the ability to show nominal rupiah currency to student with intelectual disability can be improved using the Problem Based Learning (PBL) method.